Isolation of Trichoderma sp. as a Biological Agent in the Pudak Lestari Agro Ornamental Plant Farmer Group - A. A. S. Putri Risa Andriani; Amelia Nicolas; Made Sri Yuliartini; , I Gusti Made Arjana; I Gusti Bagus Udayana; A.A.Ngurah Mayun Wirajaya; Ida Bagus Komang Mahardika (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Agro Pudak Lestari, an ornamental plant farmers group, has been cultivating chrysanthemums for an extended period. The Agro Pudak Lestari farmer group had various challenges during the growing of chrysanthemums, including inadequate yields that failed to satisfy market standards due to white rust disease. The presence of antagonistic bacteria, specifically Trichoderma sp., Implementing efficient strategies for managing white rust disease. Consequently, farmer collectives will be instructed to utilize Trichoderma sp as a biological agent. The community service initiatives conducted at the Pudak Lestari Agro Ornamental Plant Farmer Group in Pancasari Village, Sukasada District, Buleleng Regency have been executed efficiently and effectively. Partners have demonstrated a high level of awareness, up to 87%, about using Trichoderma sp mushrooms as biological agents. Additionally, farmer groups have successfully implemented techniques to get Trichoderma strains from natural sources and propagate them in the present rice cultivation medium. The Trichoderma sp fungus will be employed as a Trichocompost to mitigate the white rust disease in chrysanthemum plants, enhancing agricultural productivity.